Can Capitalists Afford Recovery? Economic Policy When Capital is Power - Shimshon Bichler; Jonathan Nitzan (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2013)
Economic, financial and social commentators from all directions and persuasion are obsessed with the prospect of recovery. The world remains mired in a deep, prolonged crisis, and the key question seems to be how to get out of it. The purpose of our paper is to ask a very different question that few if any seem concerned with: can capitalists afford recovery in the first place?
Keywords: 330; crisis; DA; economic policy; economic theory; expectations; growth; income distribution; Keynesianism; Marxism; monetarism; neoclassical economics; profit; underconsumption